PERTUMBUHAN EKONOMI INDONESIA TAHUN 2012-2020: ANALISIS PENGARUH KAPITALISASI SAHAM SYARIAH, SUKUK DAN REKSADANA SYARIAH - Novalia Sekarwangi, - (2021)
Indonesia's economic growth during the nine-year period 2012-2020 fluctuated but tended to decline. The fluctuating and slow movement caused several problems for one of the parties concerned. This study aims to look at the description and influence of the capitalization value of sharia shares, the value of outstanding sukuk and the net asset value of sharia mutual funds on Indonesia's economic growth in 2012-2020. The research method used is a quantitative method using multiple linear regression analysis with the help of SPSS version 24 software. The results of descriptive research show that Indonesia's economic growth for nine years (2012-2020) tends to fluctuate and tends to decrease, the development of the capitalization value of sharia shares for nine years (2012-2020) fluctuates but tends to increase, the development of the value of outstanding sukuk for nine years (2012-2020) always increases every year and the net asset value of sharia mutual funds for the period 2012-2020 always increases as well. The results of the hypothesis test show that the capitalization value of sharia shares, the value of outstanding sukuk and the net asset value of sharia mutual funds together affect economic growth. Partially shows that the capitalization value of sharia shares has a positive and significant effect on economic growth, then the value of outstanding sukuk has a positive and significant effect on economic growth, while the net asset value of sharia mutual funds has no effect on economic growth. Suggestions for the government, especially the OJK as the sharia capital market authority, need to develop new strategies to encourage the development of the sharia capital market, such as developing sharia capital market products and increasing literacy and inclusion of sharia capital markets, especially sharia mutual funds, so that in the future sharia mutual funds can both encourage Indonesia's economic growth.